2010
DOI: 10.1111/j.1475-3588.2009.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Youth Therapist Strategies to Enhance Client Homework Completion

Abstract: Background:  This study examined strategies youth therapists use to attempt to enhance their clients’ therapeutic homework completion. Method:  Thirty‐two youth mental health therapists participated. All participants completed a ‘Follow‐Through Strategy’ survey and 13 also participated in a semi‐structured interview. Interviews were recorded, transcribed and analysed. Results:  On the survey, therapists reported using a broad range of strategies to attempt to enhance therapeutic homework completion. Interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Praising any effort exhibited by the family, even if homework is not completed, may create honest and open discussions during the homework planning process about reasons for not completing homework, thereby keeping the momentum moving towards successful completion. A previous study found that of all therapist endorsed strategies for enhancing therapy homework completion, praising families to empower them to complete homework was the highest endorsed strategy (Houlding et al 2010). The finding that therapist use of Psychoeducation strategies in the initial phase of treatment predicted subsequent parents ’ sharing perspective on homework planning aligns with studies of predictors of overall parent engagement in child psychotherapy (Martinez et al 2015), and studies that have included psychoeducation strategies as a core component in successful parent engagement interventions (Becker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Praising any effort exhibited by the family, even if homework is not completed, may create honest and open discussions during the homework planning process about reasons for not completing homework, thereby keeping the momentum moving towards successful completion. A previous study found that of all therapist endorsed strategies for enhancing therapy homework completion, praising families to empower them to complete homework was the highest endorsed strategy (Houlding et al 2010). The finding that therapist use of Psychoeducation strategies in the initial phase of treatment predicted subsequent parents ’ sharing perspective on homework planning aligns with studies of predictors of overall parent engagement in child psychotherapy (Martinez et al 2015), and studies that have included psychoeducation strategies as a core component in successful parent engagement interventions (Becker et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Participants assigned to a pretreatment Motivational Interviewing group vs. no pretreatment prior to initiating anxiety treatment demonstrated greater homework completion, which in turn improved outcomes (Westra and Dozois 2006), and homework completion mediated the impact of the pre-treatment group on anxiety reduction (Westra et al 2009). A mixed-method study of therapeutic strategies to enhance homework completion found that therapists endorsed a broad range of strategies, such as praise, providing rationale, working collaboratively, and engaging clients through the therapeutic relationship (Houlding et al 2010). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activities that can maximize this collaboration include jointly setting and adhering to session goals or agenda, sharing the rationale for each Specific Technique with the client, eliciting and responding to client feedback and client's current mood and life events, and jointly setting, planning, and reviewing personally meaningful homework (Roth and Pilling 2008). With regard to homework in CBT, the interested reader is directed toward theory and research pertaining to the role of homework, and therapist knowledge, skills, and attitudes relevant for the effective use of homework in CBT in general (Detweiler-Bedell and Whisman 2005;Haarhoff and Kazantzis 2007;Kazantzis and Daniel 2008;Kazantzis et al 2005;Kazantzis et al 2005) and when implementing CBT with children and adolescents in particular (Gaynor et al 2006;Houlding et al 2010;Hudson andand Kendall 2002).…”
Section: Collaboratively Conducting Cbt Sessionsmentioning
confidence: 98%